Synthesis of Exocyclic Trisubstituted Alkenes via Nickel‐ Catalyzed Kumada‐Type Cross‐Coupling Reaction of gem‐ Difluoroalkenes with Di‐Grignard Reagents. Issue 2 (5th January 2016) - Dai, Wenpeng; Zhang, Xuxue; Zhang, Juan; Lin, Yingyin; Cao, Song
Abstract: A practical, nickel‐catalyzed Kumada‐type double cross‐coupling reaction of gem ‐difluoroalkenes with 1, 4‐ or 1, 5‐di‐Grignard reagents was developed. The reaction proceeded efficiently at room temperature and a variety of cyclization products, arylmethylenecyclopentanes and arylmethylenecyclohexanes, were obtained in high to excellent yields, respectively. Abstract :